2018
DOI: 10.5114/hm.2018.83103
|View full text |Cite
|
Sign up to set email alerts
|

Between-format differences and variability of technical actions during small-sided soccer games played by young players

Abstract: Purpose. This study purposes were: (i) to analyse variations of individual frequencies of technical actions between two small-sided game (SSG) formats (3 × 3 and 6 × 6) in under-8 soccer players; (ii) to test the variability of technical actions executed by very young players during 3 × 3 and 6 × 6 SSG formats. Methods. Overall, 12 young male football players (age: 7.58 ± 0.5 years; practice: 2.5 ± 0.5 years) from the same Portuguese team voluntarily participated in the study. both 3 × 3 and 6 × 6 formats were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…An interesting finding is related to the variability associated with technical actions across games (6.8-19.3% coefficient of variation) [19]. This is one of the concerns related to SSGs in youth, considering that recent studies have also revealed similarly considerable inter-and intra-session variability among youth players [5,54]. Also, in studies conducted in under-10 players [22] and professional players [21], small SSGs were associated with meaningful changes in determinant actions, such as passes, receptions, and possessions.…”
Section: Effects Of Formatmentioning
confidence: 97%
See 4 more Smart Citations
“…An interesting finding is related to the variability associated with technical actions across games (6.8-19.3% coefficient of variation) [19]. This is one of the concerns related to SSGs in youth, considering that recent studies have also revealed similarly considerable inter-and intra-session variability among youth players [5,54]. Also, in studies conducted in under-10 players [22] and professional players [21], small SSGs were associated with meaningful changes in determinant actions, such as passes, receptions, and possessions.…”
Section: Effects Of Formatmentioning
confidence: 97%
“…The inclusion criteria for the articles were: (1) relevant data concerning technical actions; (2) participants included any age group or competitive level; (3) only men were included; (4) only studies conducted in soccer players; (5) only studies published in English; and (6) only full articles. The following exclusion criteria were applied: (1) studies in women; (2) studies conducted in physical education contexts; (3) non-English articles; (4) conference abstracts, letters to the editor, errata, narrative reviews, systematic reviews, meta-analyses, or invited commentaries; (5) studies that did not include relevant data for this study or aroused serious concerns about the methodology; and (6) studies without analysis of technical actions.…”
Section: Search Strategy: Databases and Inclusion Criteriamentioning
confidence: 99%
See 3 more Smart Citations